1973
DOI: 10.1530/jrf.0.0350139
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gonadotrophin on Follicle Growth Initiation in the Neonatal Mouse Ovary

Abstract: The injection of gonadotrophin (PMSG) into mice between the ages of 3 and 6 days did not alter the number of follicles that started growth, suggesting that it did not provide the stimulus to small follicles to start their development. The injection of PMSG had no influence on small oocyte atresia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
2
1

Year Published

1978
1978
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(26 citation statements)
references
References 5 publications
3
20
2
1
Order By: Relevance
“…The PMSG did not have any marked effect on the structure of follicles, which is in general agreement with the results of Peters et al (1973) who reported that PMSG injected into mice had no effect on atresia of small oocytes or onset of growth of follicles, and Worthington and Kennedy (1979) who found that numbers of pre-antral follicles in lambs were unaffected by PMSG. In the latter study PMSG increased the number of vesicular follicles, perhaps by preventing atresia.…”
Section: Theca Externasupporting
confidence: 90%
See 1 more Smart Citation
“…The PMSG did not have any marked effect on the structure of follicles, which is in general agreement with the results of Peters et al (1973) who reported that PMSG injected into mice had no effect on atresia of small oocytes or onset of growth of follicles, and Worthington and Kennedy (1979) who found that numbers of pre-antral follicles in lambs were unaffected by PMSG. In the latter study PMSG increased the number of vesicular follicles, perhaps by preventing atresia.…”
Section: Theca Externasupporting
confidence: 90%
“…It is not clear what triggers the development-no significant changes in circulating gonadotrophin levels have been detected in our animals (Tassell et al 1978), although Foster et al (1972) reported elevations of luteinizing hormone in the post-natal period. It has been claimed that early follicular growth is independent of gonadotrophic stimulation (Peters et al 1973).…”
Section: Introductionmentioning
confidence: 99%
“…However, although many follicles are seen in the late stages of development (Jones & Krohn, 1961 ;Gates, 1971) only a small number ovulate (Ingram, 1962;Edwards et al, 1977;). An investigation of the effects of PMSG treatment on immature rats showed that, rather than increasing the numbers of large follicles, the hormone altered the balance between large and atretic follicles (Peters, Byskov, Lintern-Moore, Faber & Anderson, 1973 (McNatty, Hunter, McNeilly & Sawers, 1975) supported the previous findings and showed that an increase in FSH stimulated the granulosa cells to secrete oestradiol which in turn affected the growth of subsequent follicles (Baird, Baker, McNatty & Neal, 1975 fig. 4), whereas after 21 days of age values decrease and remain consistently low until the first preovulatory rise (Cheng & Johnson, 1974;Meijs-Roelofs et al, 1975b;Ojeda et al, 1976 (Text-fig.…”
supporting
confidence: 71%
“…In young animals there is conflicting evidence regarding the necessity of gonadotrophins for the early stages of follicular growth (Price & Ortiz, 1944;Ben-Or, 1963;Eshkol & Lunenfeld, 1971/72;Baker & Neal, 1973;Peters, Byskov, Lintern-Moore, Faber & Anderson, 1973;Challoner, 1975;Purandare, Munshi & Rao, 1976;Lintern-Moore, 1977). Regardless of the necessity of gonadotrophins to initiate follicular growth in young animals, there is considerable evidence to suggest that either gonadotrophins or oestrogen must be present to ensure the normal morphological appearance of the growing granulosa cells.…”
Section: Resultsmentioning
confidence: 99%